Asymmetric Allylation Catalyzed by Chiral Phosphoric Acids: Stereoselective Synthesis of Tertiary Alcohols and a Reagent‐Based Switch in Stereopreference. Issue 12 (5th May 2021) - Lazzarotto, Mattia; Hartmann, Peter; Pletz, Jakob; Belaj, Ferdinand; Kroutil, Wolfgang; Payer, Stefan E.; Fuchs, Michael
Abstract: The substrate scope of the asymmetric allylation with zinc organyls catalyzed by 3, 3‐bis(2, 4, 6‐triisopropylphenyl)‐1, 1‐binaphthyl‐2, 2‐diyl hydrogenphosphate (TRIP) has been extended to non‐cyclic ester organozinc reagents and ketones. Tertiary chiral alcohols are obtained with ee's up to 94% and two stereogenic centers can be created. Compared to the previous lactone reagent the stereopreference switches almost completely, proving the fact that the nature of the organometallic compound is of immense importance for the asymmetry of the product. Abstract :